Bending-shear performance of column-to-column bolted-flange connections in prefabricated multi-high-rise steel structures. (June 2018) - Liu, X.C.; He, X.N.; Wang, H.X.; Yang, Z.W.; Pu, S.H.; Ailin, Zhang
Abstract: The bolted-flange connection is a new application for mounting rectangular hollow section (RHS) columns in prefabricated multi-high-rise steel structures, which may bear the combination of bending moment and shear under permanent, live, wind loads or earthquake. The performance of the bolted-flange connection used in the structural column is different from that in its popular usage in the pipe because the subjected force is different. To investigate the bearing performance of a bolted-flange connection under the combination of bending moment and shear, this study conducted static tests and finite element analysis (FEA) of 12 column-to-column bolted-flange connections with different flange thicknesses, bolt edge distances, flange edge widths and bolt hole diameters, as well as one column without a connection. The test agreed well with the FEA, which verifies the FEA. The influences of the flange thickness, bolt edge distance, flange edge width and bolt hole diameter on the stiffness and strength of the connections, bolt tension and contact force were studied, and the failure mode and mechanism of the connection were obtained. A significant prying action occurred on the flange contact surface, increased the bolt tension in the tensile region, and caused the bolt shanks to experience tension and bending moment. The flange thickness had a large impact on the prying force, while other factors had less of an effect. Based on the yield line theory, the bearing mechanism of the connection was obtained. The formulas for the yield bearing capacity were proposed and were verified by the test and FEA. Graphical abstract: Unlabelled Image Highlights: Mechanical performance of bolted-flange connection under moment and shear Static bending and shear tests and nonlinear FEA on bolted-flange connection Effect of flange thicknesses, bolt edge distances, flange edge widths and hole size Stiffness and strength of connection, bolt tension and contact force were obtained. Yield bearing capacity obtained by proposed formulas agreed well with test and FEA.